Chiral N‐Fluorodibenzenesulfonimide Analogues for Enantioselective Electrophilic Fluorination and Oxidative Fluorination. Issue 29 (3rd September 2013) - Zhu, Chuan‐Le; Maeno, Mayaka; Zhang, Fa‐Guang; Shigehiro, Taiki; Kagawa, Takumi; Kawada, Kosuke; Shibata, Norio; Ma, Jun‐An; Cahard, Dominique
Abstract: This work describes the design, synthesis, and application of de novo chiral fluorinating agents as analogues of popular N ‐fluorodibenzenesulfonimide (NFSI). The fluorination step by means of elemental fluorine is presented. Enantioselective fluorination is demonstrated in cyclic β‐keto esters and in the synthesis of BMS‐204352 (up to 86 %  ee ). Oxidative aminofluorination is also examined. Abstract : The design, synthesis, and application of de novo chiral fluorinating agents as analogues of popular N ‐fluorodibenzenesulfonimide (NFSI) are presented. The fluorination step by means of elemental fluorine is explored. Enantioselective fluorination is demonstrated in cyclic β‐keto esters and in the synthesis of BMS‐204352 (up to 86 % ee ). Oxidative aminofluorination is also examined.